HUBUNGAN POLA KONSUMSI ALA VEGETARIAN TERHADAP LEMAK VISCERAL - Lestrina, Dini; Siahaan, Ginta; Nainggolan, Efendi (PERSATUAN AHLI GIZI INDONESIA, 2016)
Vegetarian, vegan and non-vegan, can lower the risk of metabolic syndrome disease caused by central obesity by measuring waist circumference and the general obesity by assessing Body Mass Index (BMI). One of alternative to prevent can be done by changing the pattern of diet habits from omnivores (the consumption of animal products and vegetable and dairy) become vegetarian (vegetable and dairy product consumption). The purpose of this study was to analyze differences in waist circumference and BMI in terms of nutrient intake in the vegetarian community members Indonesia Vegetarian Society (IVS) at the age of 30-58 years in Maha Vihara Maitreya Medan. This study was an observational with cross sectional design. These research subjects are divided into two groups, 42 vegans and 42 non-vegans selected by screening, and then determined by purposive sampling. Nutrient intake data collected by interview using the 24-hour recall, while the antropometry measurement using a measuring tape, scales and microtoise. Analysis were done using Independent T-test. The results showed there’s difference of waist circumference between vegan and non vegan (p = 0.008), but there is no difference of IMT (p = 0105). Statistically, energy and protein intake was not different (p> 0.05), however, there were differences found in carbohydrate intake (p = 0.001) and total fat (p = 0.005) in the vegan and non vegan. The continue research on the diet of vegan vegetarian adverse event to metabolic syndrome and the characteristics of the food based on local cultural wisdom needs to be done.